Історичні аспекти інтродукції видів роду Iris L. в Україні та перспективи їx використання в озелененні - Shvets, T.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
Data from the history of introduction of species of Iris L. genus taken from different natural floras in Ukraine, are presented. Data on prospects of the use of species of Iris L. genus in gardening are given as well.